Predicting Sports Performance among University Coaches in Ghana: The Roles of Technical and Personal Problems - Yusif Tahiru Amuda; Monday Omoniyi Moses (Indonesian Journal of Sport Management, 2025)
This study examined the association of technical and personal problems with sports performance among university coaches in Ghana. Employing a cross-sectional survey design, data from 130 coaches across 26 public universities were collected using a structured and validated questionnaire. Findings reveal a significant positive correlation between technical problems and sports performance indices (r =0.208, p = 0.009), while a significant positive correlation exists between personal problems and sports performance (r = 0.274, p = 0.002). The predictor's unstandardized coefficient (B) is 0.259, indicating that for every unit increase in technical problems, the Sport Performance Indices increase by 0.259 units. The standardised coefficient (β) is 0.208, which indicates the relative importance of the predictor. This value suggests that the predictor is the dependent variable. The t-value of 2.404 indicates that the predictor is statistically significant, with a significance level of 0.018. This means that the probability of observing this relationship by chance is less than 0.018 (or 1.8%). The 95% confidence interval for the B value ranges from 0.046 to 0.472, which does not include zero. The study underscores the need to address technical and personal factors to enhance sports performance among Ghanaian university coaches. Recommendations include investing in infrastructure, providing emotional support, and implementing strategies to improve work-life balance for university sports coaches.